Simplify: (Y3 − 5y2) ÷ Y × (Y − 1) - Mathematics

Advertisements
Advertisements
Sum

Simplify: (y3 − 5y2) ÷ y × (y − 1)

Advertisements

Solution

(y3 − 5y2) ÷ y × (y − 1)

`=("y"^3-5"y"^2)/"y"xx"y"-1`

= (y2 − 5y) × (y − 1) 

= y2 (y − 1) − 5y (y − 1)

= y3 − y2 − 5y2 + 5y

= y3 − 6y2 + 5y

Concept: Simplification of Expressions
  Is there an error in this question or solution?
Chapter 11: Algebraic Expressions - Exercise 11 (E) [Page 147]

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 11 Algebraic Expressions
Exercise 11 (E) | Q 1.13 | Page 147
Share
Notifications



      Forgot password?
Use app×